2017
DOI: 10.5123/s1679-49742017000200005
|View full text |Cite
|
Sign up to set email alerts
|

Censo de estrutura da Atenção Primária à Saúde no Brasil (2012): estimativas de coberturas potenciais*

Abstract: the findings of this study point to the great inequalities between Brazilian states in potential coverage as shown by APS structure indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
0
8
0
20
Order By: Relevance
“…Esses resultados são elucidativos da importância de considerar, em uma avaliação da ABS, a heterogeneidade na efetivação do modelo pretendido para a ABS nas diferentes áreas geográficas, tanto em termos de cobertura quanto em relação às dimensões do cuidado. Estudo sobre indicadores de estrutura dos serviços de ABS no Brasil, utilizando dados do PMAQ-AB -1º ciclo, apontou para diferenças de coberturas potenciais dos indicadores analisados entre os estados 22 . Em estudo que procurou criar uma tipologia das UBS brasileiras com base nas características estruturais das unidades concluiu-se que há importantes diferenças na distribuição das unidades de acordo com as diferentes categorias entre as regiões, estados e porte populacional dos municípios 23 .…”
Section: Resultsunclassified
“…Esses resultados são elucidativos da importância de considerar, em uma avaliação da ABS, a heterogeneidade na efetivação do modelo pretendido para a ABS nas diferentes áreas geográficas, tanto em termos de cobertura quanto em relação às dimensões do cuidado. Estudo sobre indicadores de estrutura dos serviços de ABS no Brasil, utilizando dados do PMAQ-AB -1º ciclo, apontou para diferenças de coberturas potenciais dos indicadores analisados entre os estados 22 . Em estudo que procurou criar uma tipologia das UBS brasileiras com base nas características estruturais das unidades concluiu-se que há importantes diferenças na distribuição das unidades de acordo com as diferentes categorias entre as regiões, estados e porte populacional dos municípios 23 .…”
Section: Resultsunclassified
“…Estudos indicam que o crescimento relativo da cobertura da Estratégia Saúde da Família (ESF) de 1999 a 2004 foi maior no Nordeste do que no Sul 12,13 . Na amostra estudada, a cobertura da ESF cresceu 35% ou mais em aproximadamente 65% dos municípios nordestinos, enquanto, no Sul, apenas 5% dos municípios experimentaram tal crescimento na cobertura.…”
Section: Resultsunclassified
“…9 It is important to stress that there is a clear intention to expand the FHS in the Federal District; 15-17 however, the strategy's low coverage not only persists but is also worsening: 28.6% in 2012, 14.3% in 2013. 18,10 In recent decades, there has been a significant increase in FHS coverage in Brazil as a whole, from 50.9% in 2008 to 53.4% in 2013, while its Federal District was the Federative Unit with one of the lowest coverage levels in the same period. 10 More than half of the population studied said they had not used any PHC service in the last 12 months.…”
Section: Use Of Health Services In the Federal District 2015mentioning
confidence: 99%
“…for Tertiary Care (more than a quarter) also deserves consideration. It is to be expected that a scenario characterized by the predominance of use of public hospital care services 13,20 and low PHC coverage, 10,18 as in the Federal District, will directly influence the pattern of health service use. A study by Pires et al identified that people in the Federal District use hospitals because they are close to their home or work place, and that most of the procedures carried oct in these Tertiary Health Care facilities refer to Primary Care.…”
Section: Use Of Health Services In the Federal District 2015mentioning
confidence: 99%